Providers’ perceptions of communication with patients in primary healthcare in Rwanda - Cubaka, Vincent Kalumire (PLoS One, 2018)
BACKGROUND: Delivery of effective healthcare is contingent on the quality of communication between the patient and the healthcare provider. Little is known about primary healthcare providers’ perceptions of communication with patients in Rwanda. AIM: To explore providers’ perceptions of patient-provider communication (PPC) and analyse the ways in which providers present and reflect on communication practice and problems. METHODS: Qualitative, in-depth, semi structured interviews with nine primary health care providers. An abductive analysis supplemented by the framework method was applied. A narrative approach allowed the emergence of archetypical narratives on PPC. RESULTS: Providers shared rich reflections on the importance of proper communication with patients and appeared committed to making their interaction work optimally. Still, providers had difficulty critically analysing limitations of their communication in practice. Reported communication issues included lack of communication training as well as time and workload issues. Two archetypes of narratives on PPC issues and practice emerged and are discussed. CONCLUSION: While providers’ narratives put patients at the centre of care, there were indications that patient-provider communication training and practice need further development. In-depth exploration of highlighted issues and adapted strategies to tackle communication drawbacks are prerequisites to improvement. This study contributes to the advancement of knowledge related to communication between the patient and the provider in a resource-limited setting.